The impact of gender on volleyball athletes’ self-confidence: a quantitative analysis of adolescent players in padang - Rudyanto, Rudyanto; Khairoh, Jannatul (Jurnal Patriot, 2025)
Problem: This study investigates the impact of gender on self-confidence among adolescent volleyball athletes in Padang, Indonesia, addressing a research gap in the local context where psychological aspects of training remain underexplored. Previous findings on gender-based self-confidence in sports have been inconsistent, often influenced by socio-cultural and coaching environments. Purpose: This study aims to provide empirical evidence by examining differences in self-confidence between male and female adolescent volleyball players. Method: A quantitative comparative method was employed, involving 30 participants (15 males and 15 females) aged 15–18 years, selected through purposive sampling. Athletes were assessed using a self-confidence questionnaire encompassing three dimensions: belief in skill mastery, resilience under pressure, and perceived social support. Data were analyzed using SPSS version 26 with descriptive statistics and an independent samples t-test. Results: The results showed that male athletes scored a higher mean self-confidence score (M = 172.13, SD = 24.92) compared to female athletes (M = 150.27, SD = 33.35). Levene’s test confirmed the homogeneity of variance (p > 0.05), allowing further comparison through ANOVA, which yielded F = 4.138 with a significance value of p = 0.051. Although not statistically significant, the mean difference of 21.87 points indicates a psychological trend worthy of further investigation. These findings suggest that male athletes may benefit more from current training environments, while female athletes face more variability possibly due to gender role conflict and stereotype threat. Conclusion: The study concludes that gender-sensitive coaching approaches are essential to foster balanced psychological development. Limitations include the small sample size and localized setting. Future studies should expand the population, explore mediating variables such as coach–athlete relationships, and apply mixed-methods designs. This study contributes to the development of inclusive and supportive youth sports programs in Indonesia.